Evaluation of Maxillary Sinus Volume of Class III Individuals with Different Jaw Positions by Cone-Beam Computed Tomography - Yazgı Ay Ünüvar; Emre Köse (Galenos Yayinevi, 2023)
Objective:To compare maxillary sinus volumes and surface areas among individuals with Class III skeletal patterns, with different sagittal positions of maxilla and Class I patients with normal jaw positions using cone-beam computed tomography (CBCT).Methods:CBCT images of 168 patients were analyzed retrospectively. The calculated surface areas and sinus volumes of 58 patients with Class I, normal mandibular and maxillary position (0<ANB<4, 84>SNA>80, 82>SNB>78) were compared with 61 patients with Class III retrognathic maxillary and normal mandibular positions (MRs) (ANB<0, SNA<80, 82>SNB>78) and 49 patients with Class III normal maxillary and prognathic mandibular positions (MP) (ANB<0, 84>SNA>80, SNB>82). Also, volume differences between genders and sides were investigated. One-way ANOVA and t-test were used to compare age, gender, skeletal patterns, and maxillary sinus measurements.Results:CBCT images of 94 females and 74 males were examined. There was no statistically significant difference in the right and left maxillary sinus volume and surface area measurements among Class I, Class III MR, and Class III MP groups (p>0.05). When the maxillary sinus volume and surface area were evaluated according to gender, the right maxillary sinus surface area and volume of males were found to be statistically significantly higher than those of females (p=0.012 and p=0.024). Similarly, the left maxillary sinus surface areas and volumes of males were also found to be significantly higher than those of females (p=0.000 and p=0.002).Conclusion:Different sagittal positions of the maxilla do not appear to affect maxillary sinus volume, and males tend to have greater maxillary sinus volume than females. CBCT images can be used to calculate intrabony air spaces.